1995
DOI: 10.1021/ed072p760
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Visualization of Boolean Functions: A Simple Chemical Computer

Abstract: We present a chemical realization of the Boolean functions AND, OR, NAND, and NOR with a neutralization reaction carried out in three coupled continuous flow stirred tank reactors (CSTR). Two of these CSTR's are used as input reactors, the third reactor marks the output. The chemical reaction is the neutralization of hydrochloric acid (HCl) with sodium hydroxide (NaOH) in the presence of phenolphtalein as an indicator, which is red in alkaline solutions and colorless in acidic solutions representing the two bi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

1997
1997
2019
2019

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 3 publications
0
10
0
Order By: Relevance
“…Recently, these logical functions were carried out chemically by using a neutralization reaction [44].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, these logical functions were carried out chemically by using a neutralization reaction [44].…”
Section: Introductionmentioning
confidence: 99%
“…For example, Blittersdorf built Boolean logic gates from a network of three chemical reactors in which the binary state was represented by the level of acidity. 32 In 2002, Adamatzky demonstrated that simple logic gates can be implemented using concentration waves as they constructively or destructively interfere within a given T-shape structure cut from a BZ media gel (Fig. 4d).…”
Section: Molecule-based Digitsmentioning
confidence: 99%
“…In order to perform calculations more complex than a single logical operation, it is necessary to connect multiple gates together. In the laboratory, this has often been accomplished via non-chemical means, e. g. * m.egbert@auckland.ac.nz † gagnon01@fas.harvard.edu ‡ jperezmercader@fas.harvard.edu by connecting individual gates together with tubes and pumps [9,11] or via electrical coupling. These approaches require the chemicals comprising each gate to be contained in a vessel, and assume that the chemicals in each vessel are well-stirred.…”
Section: Introductionmentioning
confidence: 99%
“…In order to perform calculations more complex than a single logical operation, it is necessary to connect multiple gates together. In the laboratory, this has often been accomplished via non-chemical means, e. g. by connecting individual gates together with tubes and pumps [9,11] or via electrical coupling. These approaches require the chemicals comprising each gate to be contained in a vessel, and assume that the chemicals in each vessel are well-stirred.…”
Section: Introductionmentioning
confidence: 99%